ANALYSIS OF OCCUPATIONAL SITTING AND LOW BACK PAIN COMPLAINTS (CASE STUDY ON TAILORS IN THE HOME INDUSTRY CONVECTION IN BANDUNG CITY) - Maharani Suyono, Annisa; Juraida, Anita (International Journal of Psychosocial Rehabilitation, 2020)
Complaints about lower back pain are common and often happen to a worker, especially workers who work in a sitting position. Some of the factors that cause lower back pain are standing or bending for a long time, sitting in an inappropriate chair or not being ergonomic, driving for a long time, poor posture, lack of exercise, obesity, pregnancy, lifting, carrying, pushing, or pulling too much weight. According to the World Health Organization (WHO), 2-5% of employees in industrialized countries experience lower back pain every year, and 15% of these employees are cargo lifters, coolies, tailors, computer operators, and jobs related to back problems. An example of work that can cause musculoskeletal disorders is sewing. In Indonesia, sewing is a job that has been occupied by both individuals and convection businesses. This research was conducted with the home industry convection tailors in Bandung. This study was an analytic observational study with a cross-sectional approach and data collection techniques, namely questionnaires and direct observation. The results of this study are the existence of a strong relationship between the tailor's sitting position variable with the perceived low back pain complaint variable with a correlation coefficient of 0.715 and a significance level